Optimization of Kampung Wisata Sawah Management Towards a Child Friendly Educational Area, Pematang Johar Village, Labuhan Deli District, Deli Serdang Regency - Yusnadi Yusnadi; Elvi Mailani; Try Wahyu Purnomo (FIP Unimed, 2021)
This Community Service Program aims to provide solutions to overcome partner problems as follows: (1) Unavailability of tour packages that offer child-friendly educational programs, (2) not optimal management of literacy rooms as child-friendly learning facilities to get to know the environment and local culture better. (local wisdom), (3) There is no child-friendly learning media that is integrated with the concept of tourism based on local wisdom, and (4) Straw waste has not been utilized to be used as tourism commodities that are innovative and based on local wisdom. The PKM program is carried out in a series of steps; (1) preparation, (2) implementation of activities, (3) monitoring and evaluation, and (4) follow-up. The methods used in this service activity include socialization, mentoring, work practices, and simulations. Activities carried out in PKM include (1) socialization and assistance in making educational tour packages, (2) mentoring in the management of literacy rooms as a means of learning for children, (3) making learning media that are integrated in concepts, and (4) assistance in making woven straw waste. Through the activities carried out, it will produce outputs in the form of an Education Fieldtrip Guidebook, Leafleats and X-Banners for Field Trip Locations, Child Friendly Literacy Rooms and X-Banners for Literacy Rooms, Educational Game Media, and Woven Straw Waste along with a Guidebook for Making Woven Straw Waste . From this activity, it is hoped that a follow-up to the Management of Rice Field Tourism Village Towards a Child-Friendly Educational Area will be realized, especially in Pematang Johar Village, Labuhan Deli District, generally in Deli Serdang Regency.